KESANTUNAN BERBAHASA KARYAWAN PT DIPA PHARMALAB INTERSAINS MANUFACTURING DIVISION KABUPATEN MAJALENGKA - Yudin, Jaki; Sabila, Elza (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2024)
Language politeness needs to be cultivated in interactions so that it runs communicatively, effectively, and does not threaten face. Therefore, adherence to language politeness is needed in order to establish good relations and cooperation, especially for employees. This study aims to describe the language politeness of PT Dipa Pharmalab Intersains Manufacturing Division Majalengka employees. The data in this study are the speeches of 7 employees in the Quality Assurance (QA) section. This study uses a qualitative approach with the technique of listening to engagement, recording techniques, and note-taking techniques. The results of this study indicate that at least Quality Assurance (QA) employees in communicating comply with the politeness principles according to Leech through the findings of 17 utterances of compliance with the maxims of tact, 7 compliance with the maxim of generosity, 11 compliance with the maxim of approbition, 14 compliance with the maxim of modesty, 28 compliance with the maxim of agreement, and 10 compliance to the maxim of sympathy.Kesantunan berbahasa perlu ditumbuhkan dalam interaksi supaya berjalan dengan komunikatif, efektif, dan tidak mengancam muka. Oleh sebab itu, pematuhan kesantunan berbahasa dibutuhkan guna terjalinnya hubungan dan kerja sama yang baik khususnya para karyawan. Penelitian ini bertujuan untuk mendeskripsikan kesantunan berbahasa karyawan PT Dipa Pharmalab Intersains Manufacturing Division Kabupaten Majalengka. Data dalam penelitian ini adalah tuturan karyawan bagian Quality Assurance (QA) yang berjumlah 7 orang. Penelitian ini menggunakan pendekatan kualitatif dengan teknik simak libat cakap, teknik rekam, dan teknik catat. Hasil penelitian ini menunjukkan bahwa setidaknya karyawan bagian Quality Assurance (QA) dalam berkomunikasi mematuhi prinsip kesantunan berbahasa menurut Leech melalui temuan 17 tuturan pematuhan maksim kebijaksanaan, 7 pematuhan maksim kedermawanan, 11 pematuhan maksim pujian, 14 pematuhan maksim kerendahan hati, 28 pematuhan maksim kesepakatan, dan 10 pematuhan maksim simpati.